2002
DOI: 10.2135/cropsci2002.4440
|View full text |Cite
|
Sign up to set email alerts
|

Losses in Wheat Due to Waterlogging

Abstract: Waterlogging stress is one of the limiting factors influencing wheat (Triticum aestivum L.) production, especially in the lower Mississippi valley. A rain‐shelter experiment was designed to evaluate the trend response of nine wheat genotypes to four levels of waterlogging treatment: 0, 10, 20, and 30 d of flooding. Genotypes planted in polyvinilchloride (PVC) containers 25 cm long by 10 cm in diameter were waterlogged in plastic tanks under controlled rain conditions. Results indicated significant linear respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
81
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 18 publications
11
81
1
1
Order By: Relevance
“…Water logging results in wilting, chlorosis, senescence and abscission of leaves which may be due to reduced uptake and mobilization of nutrients. Reduction in chlorophyll content was also reported in pigeonpea [43,44], wheat [45], maize [46] and Vigna sinensis [47]. The highly significant negative correlation between reduction in chlorophyll content and plant survival indicated that high reduction in chlorophyll after water logging and saline treatments disrupted plant metabolism which led to plant mortality.…”
Section: Discussionmentioning
confidence: 67%
“…Water logging results in wilting, chlorosis, senescence and abscission of leaves which may be due to reduced uptake and mobilization of nutrients. Reduction in chlorophyll content was also reported in pigeonpea [43,44], wheat [45], maize [46] and Vigna sinensis [47]. The highly significant negative correlation between reduction in chlorophyll content and plant survival indicated that high reduction in chlorophyll after water logging and saline treatments disrupted plant metabolism which led to plant mortality.…”
Section: Discussionmentioning
confidence: 67%
“…Mineral nutrient deficiencies and microelement toxicities at the physiological level were reported by Setter and Waters (2003) and Setter et al (2009). Waterlogging can reduce winter wheat grain yield by approximately 20 to 50%, depending on several factors, which includes the stage of crop development (Setter and Waters, 2003) and severity and duration of waterlogging (Collaku and Harrison, 2002;Malik et al, 2002). Several studies have shown that the variations in wheat yield were primarily reflected in grain number, with little influence on individual grain weight (González et al, 2005;Peltonen-Sainio et al, 2007).…”
mentioning
confidence: 99%
“…Transient waterlogging, which can impose lowoxygen stress on established plants, has been shown to reduce yield in a number of crops, including cotton (Gossypium hirsutum; Hodgson and Chan, 1982), wheat (Triticum aestivum; Collaku and Harrison, 2002), barley (Hordeum vulgare; Setter and Waters, 2003), maize (Zea mays; Mason et al, 1987), and canola (Brassica napus; Cannell and Belford, 1980). Even rice (Oryza sativa), which is well adapted to growing partially underwater, is adversely affected when the entire plant is submerged (Singh et al, 2001).…”
mentioning
confidence: 99%